A review of Métis traditional medicines in wound care with a focus on white spruce (Picea glauca), yarrow (Achillea millefolium), and broadleaf plantain (Plantago major) in Canada - Lefebvre, Amy; Moise, Alexander R.; Manitowabi, Darrel (Ethnobotany Research and Applications, 2026)
Background: Skin injuries have been documented across the globe for centuries and are a common health concern worldwide. Although many methods have evolved to heal lacerations, traditional Métis medicines have remained underexplored in literature. This review aims to provide an overview of the common plants used by the Métis in wound care. Due to their consistent documentation across Métis oral histories and proximity to Métis homelands, white spruce (Picea glauca), yarrow (Achillea millefolium), and broadleaf plantain (Plantago major) offer insight into the applications of Métis medicines. Methods: A narrative literature review was conducted using academic databases to identify primary and secondary sources on Métis traditional medicines and their wound care applications. Both ethnobotanical and biomedical studies were included to capture cultural and pharmacological perspectives. Results: In P. glauca, the lignan 7-hydroxymatairesinol demonstrates anti-inflammatory properties that may support wound healing. A. millefolium contains natural antioxidants and linoleic acid that can reduce infection risk and help restore skin elasticity in later healing stages. P. major contains aucubin and allantoin, compounds associated with accelerated cellular regeneration. Studies suggest that integrating these traditional medicines into modern wound dressings may help reduce complications and improve healing outcomes. Conclusion: This review highlights the therapeutic potential of Métis medicines in wound care. Future research should include collaboration with Métis knowledge holders and clinical studies to validate efficacy, determine safe dosages, and explore culturally respectful integration into modern biomedical practice. Keywords: Wound care, Métis, traditional medicine, spruce, yarrow, plantain, Canada